IMPLEMENTASI PROGRAM COOPERATIVE AND ASSISTANCE FOR RELIEF EVERYWHERE (CARE) INTERNATIONAL DALAM MEMPERBAIKI KEHIDUPAN SOSIAL PEREMPUAN DI INDIA TAHUN 2013-2015 - Norwi, Peggy Putri; Pakpahan, Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research explains about implementation programs of Cooperative and Assistance for Relief everywhere (CARE) International to repair the social life of Women and Girls in India. India is one of countries in the world which have many problems about women and gender. CARE International with their confederations in India so concern about women problems in India.Data of this research analyzed by applying groups behavior which is International non-governmental organization (INGO) as level of analysis. This research use Pluralism perspective and use International Organizations theory which is introduced by Clive Archer that show the role of International Oranizations which are divided into three that are as instrument, as arena and as independent actor.This research show how CARE International as a non-profit INGO engaged in humanitarian take an action in improving the social life of Women and Girls in India with programs specifically designed for the empowerment of women and Girls in India.Keywords: CARE International, CARE India, Women, Girls, Gender